IMPROVING THAI STUDENTS’ ERRORS IN ENGLISH NEWS HEADLINE TRANSLATION THROUGH NOTICING AND CALL - Amporn Sa-ngiamwibool (University of Muhammadiyah Purwokerto, 2010)
Insufficient knowledge of English is one of the major problems that Thai students face in translating from Thai into English and the kinds of knowledge individual students lack are different. To deal with this, instructors need tools that can solve the problems each student is facing. Computer-assisted language learning (CALL), which encourages independent learning, was introduced as a tool to facilitate individual students’ English language learning of all types, including translation. The main purpose of this study was, therefore, to investigate how CALL could improve the Thai students’ translation skill. News headlines convey the gist of the news and have distinctive syntactic properties, newspaper headlines were therefore chosen for this study. The findings reveal that, first; the types of errors that Thai students made in translation were wrong use/translation, omission, and redundant use. In terms of linguistics, they made grammatical, discourse, and lexical errors. Second, noticing in cooperation with CALL can reduce those errors significantly. Third, the students showed their highly positive attitude toward using CALL to improve their translation skills. Fourth, the learner-centered, independent learning method was effective for solving individual students’ problems in translation. Finally, the use of CALL not only enhances the students’ translation skill but also encourages independent language learning effectively.